Capital Asset Pricing Model (CAPM) And Its Implications For Investment Decision Making In LQ45 Companies On The Indonesia Stock Exchange - Villa Maharani Aslim; Wisang Candra Bintari; Mitta Muthia Wangsi; Bekti Wiji Lestari; Nur Aeni Waly (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to determine the level of stock returns and risks, as well as the grouping and assessment of efficient and inefficient stocks in the LQ 45 index using the Capital Asset Pricing Model (CAPM) method in determining stock investment decisions in the LQ 45 index for the 2019-2023 period. The type of research used is a quantitative approach with a descriptive method. The data source used is secondary data, the sampling technique uses non-probabilistic sampling, namely purposive sampling, resulting in 23 stock samples examined on the Indonesia Stock Exchange website. The results of the study, determined using the Capital Asset Pricing Model (CAPM), show that of the 23 sample companies in the LQ 45 index in 2019, there were 14 efficient stocks in 2019, 16 efficient stocks in 2020, 8 efficient stocks in 2021, 15 efficient stocks in 2022, and 5 efficient stocks in 2023. These shares are included in the efficient share classification because they have an expected return [E(Ri)] that is lower than the individual return (Ri) which indicates a positive value so that based on calculations using the CAPM method, it is recommended that the decision taken by investors is to buy shares.